Inventarisasi dan Identifikasi Serangga Predator pada Padi di Kabupaten Ogan Ilir, Sumatera Selatan - Hawaryah Istiqomah; Dea Abbellia; Lusy Triani; Nabella Mevika; Safira Siti Khodijah; Yuliana Yuliana; Abu Umayah; Bambang Gunawan; Arsi Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Istiqomah H, Abbellia D, Triani L, Mevika N, Khodijah SS, Yuliana Y, Umayah A, Gunawan B, Arsi A. 2022. inventory and identification of rice predator insects in Ogan Ilir District, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 552-561. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Rice (Oryza sativa) is one of the plants that is an important commodity in Indonesia, various efforts have been made to increase rice production, but often encounter obstacles, one of which is the presence of organismal pests, especially insects. Therefore, it’s necessary to have the role of natural enemies in the form of predatory insects in controlling rice pests. This study aimed to determine the number and types of predatory insects found in rice plants in three villages, namely Muara Penimbung Village, Tanjung Sejaro Village, Sakatiga Village, Indralaya District, Ogan Ilir Regency, South Sumatra. This research method was carried out by observing and using yellow traps installed in the rice fields to catch predatory insects. From the research results in the three villages, there are predatory insects with four different orders, namely the order Odonata, order Coleoptera, order Hemiptera, and order Diptera. The order Odonata (dragonfly) consists of 4 species: Pantala flavescents, Orthetrum sabina, Agriocnemis minima, Orthetrum Chrysis. Then the order Coleoptera (beetle) found consisted of 4 species: Epilachna admirabilis, Paederus fuscipes, Micraspis discolor, Diekeana admirabilis. order Hemiptera found 1 species, namely: Andrallus spinidens. One species of the order Diptera, namely: Asilidae sp. So, it can be concluded that predatory insects on rice plants are very diverse and consist of various orders that can be used as natural enemies to control insect pests or plant pests. Further education is needed about the important role of predatory insects as natural enemies of plant pest control.